2019
DOI: 10.1101/2019.12.17.880252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abundances of transcripts, proteins, and metabolites in the cell cycle of budding yeast reveals coordinate control of lipid metabolism

Abstract: Establishing the pattern of abundance of molecules of interest during cell division has been a long-standing goal of cell cycle studies. In several systems, including the budding yeast Saccharomyces cerevisiae, cell cycle-dependent changes in the transcriptome are well studied. In contrast, few studies queried the proteome during cell division, and they are often plagued by low agreement with each other and with previous transcriptomic datasets. There is also little information about dynamic changes in the lev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Recent work by Blank et al (10), using an alternative approach of elutriation to study the yeast cell cycle, also found notable dynamic changes in metabolism through changes in enzyme abundance. Despite different experimental approaches used, several findings are shown to be reflected in both our studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Blank et al (10), using an alternative approach of elutriation to study the yeast cell cycle, also found notable dynamic changes in metabolism through changes in enzyme abundance. Despite different experimental approaches used, several findings are shown to be reflected in both our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Systems biology studies of the eukaryal model organisms, budding and fission yeast, during their cell cycle has previously afforded insight into the relationship between the transcriptome and proteome (4,5), and the proteome and phosphoproteome (6, 7), adding to related work that has focused on individual omic studies of the metabolome (2) and the transcriptome (8,9). Recent relative quantification of the proteome, transcriptome, and metabolome of budding yeast (10) has also added to this growing body of work for understanding cell division in eukaryal organisms. Here we performed absolute quantitative measurements of the transcriptome and proteome, alongside semiquantitative analysis of the phosphoproteome and metabolome, to identify and clarify key changes during cell division, shedding light on how different processes may be regulated from a multiomic perspective.…”
mentioning
confidence: 99%